Fatty acids in beef from grain- and grass-fed cattle: the unique South African scenario. Issue 2 (31st May 2016) - Hall, N; Schönfeldt, HC; Pretorius, B
Abstract: Objective: Different fatty acids elicit different responses in the human body once ingested. Although red meat is often considered to be a source of fatty acids which has a negative impact on human health, many studies have reflected variability in the quantity and quality of fatty acids found in red meat produced on different production systems in different countries. This study evaluated the fatty acid profile of beef, produced by the grass- and grain-fed production systems practised in South Africa. Design: Data are reported as a percentage of lipid per 100 g total fat to enable a comparison with international findings. Furthermore, the findings are translated into edible meat portions, taking fat trimming (often associated with red meat intake) into consideration in order to determine the contribution which the different products can make to the human diet. Subjects and setting: Three cuts of beef from cattle from four production groups were sampled and the fatty acid composition analysed for the meat and fat fractions. Results: Notable differences were found in the quantity and quality of different fatty acids in beef from the different production systems. When untrimmed, no statistically significant difference was found in the total fat between beef produced on the different production systems. Differences became more significant as trimming was performed. When trimmed of all visible fat, beef from young cattle fed according to a grain-based feeding system contained less total fat (6.96 g), and less saturated fat (2.16 g) per 100 g, than beef produced from their grass-fed counterparts (9.77 g and 3.30 g, respectively). There was a more favourable omega-6 to omega-3 fatty acid ratio, i.e. 2.0–2.5:1.0 for grass-fed cattle, compared to 8–30:1 for grain-fed cattle, irrespective of the degree of trimming. The beef from the grass-fed cattle also contained a higher quantity of conjugated linoleic acid. Conclusion: A unique classification system for red meat has been implemented in South Africa and dictates the characteristics of the fresh meat that is available to consumers. The results of this study consequently indicate distinctive differences between the fatty acid profile of local red meat and that of beef produce from other countries; often used as a reference for dietary guidance.